PELATIHAN ANAK SEKOLAH MINGGU DALAM MENINGKATKAN KOSAKATA BAHASA INGGRIS DAN KESADARAN MULTIKULTURAL MELALUI DRAMA BERBASIS ALKITAB - Kakerissa, Wenda Marlin (LPPM STAI Muhammadiyah Probolinggo, 2025)
The training aims to enhance Sunday School children's vocabulary and cultural knowledge via the enactment of Bible stories. As part of community-based service, this strategy is utilized. A contextual and interactive learning process is integrated with the values of love and tolerance, as well as cultural, religious, and linguistic variety. To gauge the extent to which their vocabulary has grown, twenty-one students from the pre-teens and teenagers groups completed both the pre- and post-tests. Twenty-seven children participated in the program evaluation. Each student received an additional 1.90 points, or 19.05% of the maximum possible score, according to the findings. Two children have maintained a perfect score since the pre-test. These findings support the idea that drama training grounded in the Bible can be an effective means of expanding one's vocabulary and fostering cross-cultural understanding. The assessment also revealed that the children were highly engaged and joyful. This is a great opportunity for religious organizations to impart their ideals and language in a manner consistent with their doctrine. Keywords: Sunday school students, training, play, English language, cultural awareness.